Sinalizando a cartografia para dar sentido na geografia para surdos - Mazzarollo, Thiago Rafael (2017)
Although the social inclusion of people with disabilities is a usual theme, it is not completely resolved. In the school environment, teachers and the educational staff sometimes feel unprepared to such commitment. In this regard, the beginning of academic life also has limits and weaknesses, even though special education teaching is a method that passes indistinctly through all the educational levels. Therefore, the search for indicatives with possible contributions in this area has motivated this study, which also characterizes the need to specify the deaf in its linguistic and methodological uniqueness. Since 2002, with the approval of the Law 10.436, the inclusion of deaf students in regular schools became an impressive situation, and since then the need of meeting the students needs appropriately has been increasing. The aim of this study is to discuss the difficulties and limitations to the understanding of the cartography concepts in the Geography teaching, as well as in the Brazilian sign language (known as Libras). This research presents the elements of the special education history with a special look at the teaching of the deaf, in the process of knowledge construction compared to the elementary concepts in cartography in the Geography teaching. To that, through bibliographic reviews, it was important to cover three general themes: a) Special Education, as based in the authors Bianchetti (1995), Jannuzzi (2004), Mendes (2002 and 2010) and Mazzotta (2011); b) Deaf , Education and Brazilian Sign Language (Libras), in the works of Brito (1995), Quadros and Karnopp (2004), Perlin and Strobel (2006), Fernandes (2007) and Godelfeld (2010); and c) Cartography and Geography teaching with Francischett (2002, 2004, 2009 and 2010), Martinelli (2007 and 2009), Castrogiovanni (1994 and 2007) and Loch (2006). The information and historic withdrawals about the deaf education in Francisco Beltrão were obtained through interviews with a city pioneer, who has two deaf children that needed special education. Two teachers, who began this special education project with the deaf in the town were also interviewed and shared their experiences about that time. Three deaf people also contributed to this study giving information and reporting experiences they had during their education process. Therefore, Geography classes were watched having two deaf students regularly enrolled. These classes were watched at Colégio Estadual Eduardo Virmond Suplicy, which has Primary, Secondary School and Vocational Education, being a reference institution in the teaching of deaf students, located in Francisco Beltrão/ PR. Throughout interviews, were surveyed the Geography teacher and the Brazilian sign language interpreter who worked with the included students. The results brought meaning and important elements, specially about the necessity of discussing this subject heavily, on the basis of practical and punctual actions. Another aspect was the urgent necessity of teaching materials, to needy students as well, to complement the pedagogical action. In the object framework, the linguistic need was evidenced in Cartography to help with the concepts and geographic contents, and the contributions of this study resulted in a glossary presentation with aspects pointed and highlighted with great importance, which can diminish the problems and help in the process of teaching deaf people.